A common genetic background could explain early-onset Crohn's disease. - Bianco, Anna Monica; Zanin, Valentina; Girardelli, Martina; Magnolato, Andrea; Martelossi, Stefano; Martellossi, Stefano; Tommasini, Alberto; Marcuzzi, Annalisa; Crovella, Sergio (Med Hypotheses, 2012)
Crohn's disease (CD) is a multifactorial disease, in which environmental, microbial and genetic factors play important roles. CD is characterized by a chronic granulomatous inflammation by necrotic scarring with aspects of full-thickness wall. In spite of affecting mainly young adults, sometimes, CD can be present in the first year of life (early onset Crohn disease, EOCD) showing an unpredictable course and being often more severe than at older ages. In this paper we propose the hypothesis that EOCD patients should be analyzed using a Mendelian approach with family studies aimed to identify new loci directly involved in the early onset Crohn's disease. So we will leave the classic association study approach used until now for the identification of genes responsible for susceptibility to CD and propose linkage family analysis as alternative and powerful tool for the identification of new genetic variants associated with familiar cases of EOCD.
Keywords: Crohn Disease; Genetic Linkage; Genetic Predisposition to Disease; Humans; Models, Biological